Strategi Pemimpin Kristen dalam Penguatan Iman Jemaat di Tengah Kasus Konversi Agama - Situmeang, Chintya Megaria; Sagala, Ronal; Tambunan, Alki; Giawa, Jui (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This study aims to discuss the strategies carried out by Christian leaders (in this case the Pastor) in strengthening the faith of the congregation in the midst of religious conversion cases that occur in Simangumban sub-district, North Tapanuli district. Christian leaders (in this case the Pastor) have a role to strengthen the faith of the congregation in the midst of cases of religious conversion. The method used in this research is the case study method. The results showed that Christian leaders have carried out various strategies to strengthen the faith of their congregation members, both preventive strategies through faith debriefing since Sunday School, worship and categorical meetings, sermons, catechization, pastoral visits, debriefing of Elders, as well as repressive strategies through the provision of church tactics law and the reading of the Panguhuman na Dokdok Situtu Agenda in front of the entire congregation to members of the congregation who converted.